Transcriptional landscapes underlying Notch-induced lineage conversion and plasticity of mammary basal cells - Merle, Candice; Rodrigues, Calvin; Pourkhalili Langeroudi, Atefeh; Journot, Robin; Rost, Fabian; Dang, Yiteng; Rulands, Steffen; Fre, Silvia (The EMBO journal, 2025)
The mammary epithelium derives from multipotent mammary stem cells (MaSCs) that engage into differentiation during embryonic development. However, adult MaSCs maintain the ability to reactivate multipotency in non-physiological contexts. We previously reported that Notch1 activation in committed basal cells triggers a basal-to-luminal cell fate switch in the mouse mammary gland. Here, we report conservation of this mechanism and found that in addition to the mammary gland, constitutive Notch1 signaling induces a basal-to-luminal cell fate switch in adult cells of the lacrimal gland, the salivary gland, and the prostate. Since the lineage transition is progressive in time, we performed single-cell transcriptomic analysis on index-sorted mammary cells at different stages of lineage conversion, generating a temporal map of changes in cell identity. Combining single-cell analyses with organoid assays, we demonstrate that cell proliferation is indispensable for this lineage conversion. We also reveal the individual transcriptional landscapes underlying the cellular plasticity switching of committed mammary cells in vivo with spatial and temporal resolution. Given the roles of Notch signaling in cancer, these results may help to better understand the mechanisms that drive cellular transformation. Synopsis Basal-to-luminal lineage plasticity can be triggered by ectopic Notch, but the conservation and mechanistic details of this phenotype remain unclear. This study reports how Notch-driven cell fate conversion ensues across multiple mouse bi-layered epithelia, and reveals a role for cell proliferation in lineage conversion. Constitutive Notch activation in adult basal cells induces a switch from to luminal fate in mouse mammary, salivary, lacrimal and prostatic glands. Individual transcriptional states of index-sorted cells during basal-to-luminal conversion progress stepwise and asynchronously via two distinct intermediate cell states. Ectopic Notch-induced luminal hormone-responsive cells differ from their wild type counterparts, in promoting the growth of hyperplastic lesions in vivo. Cell proliferation is indispensable for Notch-driven cell-identity switching, ruling out a transdifferentiation event. Notch1-triggered basal-to-luminal fate switching is progressive, conserved across bi-layered mammalian epithelia, and involves cell proliferation.